Patterns of gene transcript abundance in the blood of children with severe or uncomplicated dengue highlight differences in disease evolution and host response to dengue virus infection. - Long, H; Hibberd, M; Hien, T; Dung, N; Van Ngoc, T; Farrar, J; Wills, B; Simmons, C (2009)
DNA microarrays and specific reverse-transcription polymerase chain reaction assays were used to reveal transcriptional patterns in the blood of children presenting with dengue shock syndrome (DSS) and well-matched patients with uncomplicated dengue. The transcriptome of patients with acute uncomplicated dengue was characterized by a metabolically demanding "host-defense" profile; transcripts related to oxidative metabolism, interferon signaling, protein ubiquination, apoptosis, and cytokines were prominent. In contrast, the transcriptome of patients with DSS was surprisingly benign, particularly with regard to transcripts derived from apoptotic and type I interferon pathways. These data highlight significant heterogeneity in the type or timing of host transcriptional immune responses precipitated by dengue virus infection independent of the duration of illness. In particular, they suggest that, if transcriptional events in the blood compartment contribute to capillary leakage leading to hypovolemic shock, they occur before cardiovascular decompensation, a finding that has implications for rational adjuvant therapy in this syndrome.